Síntesis de nanopartículas de cobre para el control de hongos fitopatógenos - Pariona y Cols., Nicolaza (2019)
Phytopathogenic fungi are one of the biggest problems affecting the agricultural sector, causing losses that exceed billions of dollars per year. In addition to this, antifungal resistance hinders the control of phytopathogenic fungi and it is necessary to find control alternatives of low cost that do not contaminate the environment. Therefore, the main objective of this project was to synthesize copper nanoparticles (NPs-Cu) and evaluate their antifungal activity against different phytopathogenic fungi. NPs-Cu were synthesized by the reduction method and characterized by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The antifungal activity evaluation of the NPs-Cu was carried out against five species of phytopathogenic fungi (Fusarium solani, Fusarium verticillioides, Verticillium dahlie, Neofusicoccum sp, and Fusarium oxysporum). The results showed that the antifungal effect of NPs-Cu depends on the concentration used and species of fungus. Therefore, the NPs-Cu obtained have potential application to control phytopathogenic agents.